2007
DOI: 10.1007/s10071-006-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Spider monkey ranging patterns in Mexican subtropical forest: do travel routes reflect planning?

Abstract: Although it is well known that frugivorous spider monkeys (Ateles geoffroyi yucatanensis) occupy large home ranges, travelling long distances to reach highly productive resources, little is known of how they move between feeding sites. A 11 month study of spider monkey ranging patterns was carried out at the Otochma'ax Yetel Kooh reserve, Yucatán, Mexico. We followed single individuals for as long as possible each day and recorded the routes travelled with the help of a GPS (Global Positioning System) device; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 21 publications
3
61
0
4
Order By: Relevance
“…This result resonates with recent empirical findings on primate systems, where no evidence for multi-step planning was found [12]. However, this issue is not completely settled, as other studies suggest that multiple-step planning is sometimes used by primates [13]. Some experiments even provide evidence that bumblebees are able to solve the TSP by learning from experience, but in simple configurations containing a small number of targets [14].…”
Section: Discussionsupporting
confidence: 85%
“…This result resonates with recent empirical findings on primate systems, where no evidence for multi-step planning was found [12]. However, this issue is not completely settled, as other studies suggest that multiple-step planning is sometimes used by primates [13]. Some experiments even provide evidence that bumblebees are able to solve the TSP by learning from experience, but in simple configurations containing a small number of targets [14].…”
Section: Discussionsupporting
confidence: 85%
“…Thus, human spatial search in this random environment is not random. This conclusion is also bolstered by prior studies demonstrating that numerous animals remember spatial locations to produce nonrandom spatial search patterns in the wild (20,(35)(36)(37)(38)(39)(40)(41). We also found that the distribution of path lengths in phase 1 was significantly different from that in phase 2 ( Fig.…”
Section: [2]mentioning
confidence: 58%
“…Are primates able to find these trees, and how efficient are they at doing so? A number of studies found that wild primates were more efficient in finding food than predicted by random search models, suggesting that individuals use some mental heuristics to locate food (e.g., Cunningham, 2003;Garber & Hannon, 1993;Janson, 2000;Milton, 2000;Valero & Byrne, 2007). In our own studies on gray-cheeked and sooty mangabeys (Lophocebus albigena johnstonii; Cercocebus atys atys), we found that monkeys were more likely to approach and search for fruit under or in trees that had produced fruits than empty trees of the same species (Janmaat et al, 2006b;Figs.…”
Section: How Do Forest Primates Know Where To Find Fruit?mentioning
confidence: 99%
“…It is important to consider that the shortest route is not always the most efficient one, and that animals could combine different goals in one single route, and that they could monitor food without exploiting it (Sigg & Stolba, 1981). Some researchers have generated geometric or step models combined with sophisticated statistics to determine the likelihood of whether spatial representations are involved in travel decisions (Bates, 2005;Cunningham & Janson, 2007;Garber & Hannon, 1993;Janson, 1998;Milton, 2000;Noser & Byrne, 2007a;Valero & Byrne, 2007).…”
Section: Spatio-temporal Mental Representations In the Natural Habitatmentioning
confidence: 99%